Doskonalenie rdzenia systemu zarządzania organizacją - Cyfert, Szymon (The management system core improvement, 2006)
The aim of this article is to discuss the sequence of events in the process of the core management system improvement. The article starts with presentation of idea of management system cohesion. This helps to define the core of management system and then to derive the sequence of its improvement.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 440-446